AN ANALYSIS OF LIFE SKILLS’ SPORTS STUDENTS BASED ON GENDER AND DOMICILE - Anira, Anira; Syarifatunnisa, Syarifatunnisa; Ma’mun, Amung (Universitas Pendidikan Indonesia, 2021)
This study sought to identify the life skills of sports students based on gender and place of residence. 97 Indonesian sports students that participated in the study's intake class technique served as the sample. The data is gathered using the LSSS (Life Skills Scale for Sports). The Independent Sample t-test from SPSS version 22 was analyzed using the ex post facto approach. This study's findings show no statistically significant difference in life skills between genders (p = 0.101) and significant differences between domiciles (p = 0.013). It is proposed that additional research examine the how and why of these findings.